2015
DOI: 10.1371/journal.pone.0133043
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Awareness, Attitudes and Practices Regarding Common Eye Diseases in the General Population in a Rural District in Bangladesh: The Bangladesh Population-based Diabetes and Eye Study (BPDES)

Abstract: BackgroundTo assess the awareness, attitudes, and practices associated with common eye diseases and eye care utilization in a rural district of Bangladesh.MethodsData were collected using a multilevel cluster random sampling technique from 3104 adults aged ≥30 years from the Banshgram union with a questionnaire assessing the awareness, attitudes and practice about diabetes and common eye diseases, educational attainment, socio-economic status, and medical history.ResultsParticipants were aged between 30 and 89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
62
7
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 29 publications
12
62
7
2
Order By: Relevance
“…Our finding of a higher prevalence of disability among females than males is consistent with previous studies [3, 31, 32]. This pattern could be explained by a variety of factors, including the fact that females in low income countries are more likely to have poor health and functional disabilities [33], to have low educational attainment and hence making them less knowledgeable about risk factors and management of disease and differential access to care, especially if the care facilities are far away from their residence [11, 34, 35]. In addition, women continue to be victims of physical violence or domestic abuse by their partners, relatives or neighbors and this may have an impact on the prevalence of disability.…”
Section: Discussionsupporting
confidence: 90%
“…Our finding of a higher prevalence of disability among females than males is consistent with previous studies [3, 31, 32]. This pattern could be explained by a variety of factors, including the fact that females in low income countries are more likely to have poor health and functional disabilities [33], to have low educational attainment and hence making them less knowledgeable about risk factors and management of disease and differential access to care, especially if the care facilities are far away from their residence [11, 34, 35]. In addition, women continue to be victims of physical violence or domestic abuse by their partners, relatives or neighbors and this may have an impact on the prevalence of disability.…”
Section: Discussionsupporting
confidence: 90%
“…Other researchers identified that education level, socioeconomic status and being female are positively associated with an awareness of diabetes and colorectal cancer. 16,17 Similar findings were demonstrated by Islam et al, 18 in examining factors affecting the awareness of eye disease. Given these findings, we expect that demographic factors have a significant impact on awareness of second-hand smoke.…”
Section: Introductionsupporting
confidence: 59%
“…27 However, previous studies focusing on awareness of diseases found that socioeconomic status is positively associated with level of awareness. [16][17][18]28 It can, thus, be concluded that wealth index and socioeconomic status have different impacts on second-hand smoke awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies assessed awareness of DR (or awareness that diabetes can affect the eye) in the general population (Table ). Awareness was highly variable, ranging from 4% in a study in Bangladesh to 86.2% in Iran . Specific knowledge about the disease was also low, although increased socioeconomic status, education and urban living were associated with increased DR knowledge.…”
Section: Resultsmentioning
confidence: 99%